Reproductive biology of the Egyptian free-tailed bat, Tadarida Aegyptiaca - Tsita, Johannes Ngoako (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1994)
The reproductive biology of Tadarida aegyptiaca was studied using specimens collected in the Cape Province of South Africa. The morphology of the reproductive tract of the species was generally similar to that of other molossids, however, the absence of Cowpers glands was unusual. Spermatogenesis began in February and spermatozoa were released to the cauda epididymis during August and September. Follicular development started in March and culminated with the appearance of Graafian follicles in July. Ovulation probably occurred in August and specimens were pregnant by September. Gestation length was estimated to be four to five months and a single young was born in December. The data suggest that T. aegyptiaca is monotocous and monoestrous.
Keywords: Tadarida aegyptiaca -- Reproduction; Bats -- Reproduction